The Icelandic Fishing Industry: a Comprehensive Overview Until the end of 2001 - Ögmundur H. Knútsson 1962-; Helgi Gestsson 1949- (Viðskiptadeild Háskólans á Akureyri, 2006)
This paper gives a short but comprehensive overview of the Icelandic fish industry, its history, development and structure until the end of the year 2001. The definition of a fish industry will focus on catching (the fishing sector and fish farming), processing and export. The paper reveals a revolutionary development in the Icelandic fish industry from a supplement to farming in the Middle Ages to a modern high-tech industry. The fish industry in Iceland is at present one of the central industries in the country, and has a leading position in the world. The authors argue that these developments have been brought about by structural transformations, such as the introduction of a quota system, technical development, deregulation and privatisation, mergers and increased concentration, as well as changes in export and marketing. JEL classification: O3, Q22 Keywords: Fishing industry, Iceland, catching, processing, export